2009
DOI: 10.3324/haematol.13733
|View full text |Cite
|
Sign up to set email alerts
|

Shwachman-Diamond syndrome neutrophils have altered chemoattractant-induced F-actin polymerization and polarization characteristics

Abstract: delayed in SDS neutrophils. This is the first study revealing a molecular defect, namely defective F-actin cytoskeletal remodeling, which may contribute to impaired chemotaxis in SDS patients. Design and Methods Neutrophil isolation and cell cultureBlood was obtained after informed consent of healthy volunteers (26-43 years) and SDS patients (2-29 years; all with mutations 183-184 A>CT [K62X]/IVS2 258+2T>C [C84fs]). The study was approved by the Medical Ethics Committees of the AMC Hospital and the institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 26 publications
6
42
0
3
Order By: Relevance
“…Although tra- patients, including profound neutropenia and defective exocrine pancreas development. Neutrophils of SDS patients have been reported to show impaired chemotaxis and migration deficiency (34,35), which lead to repeated infections, as was also observed in all 3 patients reported here. In accordance with the results of these studies, we observed a decrease in the capacity of neutrophils to migrate toward the injury site in the zebrafish model ( Figure 5).…”
Section: Discussionsupporting
confidence: 63%
“…Although tra- patients, including profound neutropenia and defective exocrine pancreas development. Neutrophils of SDS patients have been reported to show impaired chemotaxis and migration deficiency (34,35), which lead to repeated infections, as was also observed in all 3 patients reported here. In accordance with the results of these studies, we observed a decrease in the capacity of neutrophils to migrate toward the injury site in the zebrafish model ( Figure 5).…”
Section: Discussionsupporting
confidence: 63%
“…21,22 The SBDS homolog in Dictyostelium discoideum, an amoeba model to study neutrophils, is enriched in pseudopods of migrating cells, 38 further implicating a role for SBDS in chemotaxis. Migration of monocytes/ , WT and Sbds-null nuclear extracts, whereas the mutant consensus oligonucleotide had no effect (n ϭ 4): *P Ͻ .005; **P Ͻ .01.…”
Section: Migration Is Impaired In Rac2-deficient Sbds-ablated Cellsmentioning
confidence: 99%
“…20 In addition to concerns of neutropenia and recurrent infections, neutrophils of affected persons have been shown to exhibit impaired chemotaxis and deficiency in migration. 21,22 A lesscharacterized abnormality with SDS patients is their defect in bone homeostasis, a parameter that is normally maintained via the balanced activities of bone-producing osteoblasts and boneresorbing osteoclasts. 23 A unique feature of osteoclast formation, or osteoclastogenesis (OCG), involves multiple fusions of preosteoclasts derived from cells from the monocyte-macrophage lineage, a process requiring a dynamic actin cytoskeleton that is regulated by small GTPases.…”
Section: Introductionmentioning
confidence: 99%
“…The bone marrow is typically mildly dysplastic and hypocellular. Abnormalities of neutrophil chemotaxis have been reported, 55,56 though patients are able to form purulent abscesses and empyemas. 57 Neutrophil respiratory burst activity is normal.…”
Section: Shwachman-diamond Syndrome: Clinical Featuresmentioning
confidence: 99%